Conductive elastomer composites for fully polymeric, flexible bioelectronics - Cuttaz,E; Goding,J; Vallejo-Giraldo,C; Aregueta-Robles,U; Lovell,N; Ghezzi,D; Green,RA (Biomaterials Science, 2019)
Flexible polymeric bioelectronics have the potential to address the limitations of metallic electrode arrays by minimizing the mechanical mismatch at the device-tissue interface for neuroprosthetic applications. This work demonstrates the straightforward fabrication of fully organic electrode arrays based on conductive elastomers (CEs) as a soft, flexible and stretchable electroactive composite material. CEs were designed as hybrids of polyurethane elastomers (PU) and poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS), with the aim of combining the electrical properties of PEDOT:PSS with the mechanical compliance of elastomers. CE composites were fabricated by solvent casting of PEDOT:PSS dispersed in dissolved PU at different conductive polymer (CP) loadings, from 5 wt% to 25 wt%. The formation of PEDOT:PSS networks within the PU matrix and the resultant composite material properties were examined as a function of CP loading. Increased PEDOT:PSS loading was found to result in a more connected network within the PU matrix, resulting in increased conductivity and charge storage capacity. Increased CP loading was also determined to increase the Young's modulus and reduce the strain at failure. Biological assessment of CE composites showed them to mediate ReNcell VM human neural precursor cell adhesion. The increased stiffness of CE films was also found to promote neurite outgrowth. CE sheets were directly laser micromachined into a functional array and shown to deliver biphasic waveforms with comparable voltage transients to Pt arrays in in vitro testing.